The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/1983-21252022v35n214rc
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Aspects of Yellow Passion Fruit With Use of Hydrogel and Mulching

Abstract: In the Brazilian semi-arid region, water deficit is one of the main factors that compromise the growth and productive yield of crops, including yellow passion fruit, due to the limitation of carbon assimilation by the photosynthetic activity of plants. Therefore, it is necessary to manage the soil with technologies that can reduce the loss of water in the soil and mitigate the effects of water deficit on yellow passion fruit plants cultivated under semi-arid conditions. The objective of this study was to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Hydro-absorbent polymers can absorb and retain a large amount of water and fluids, reducing nutrient losses by leaching, such as nitrogen, which is a constituent element of chlorophyll molecules (Felippe et al, 2016(Felippe et al, , 2020 and is present in fertilizers such as urea and organic matter. Comparable results were obtained by Araújo et al (2022) in yellow passion fruit cv. BRS GA1 irrigated in soil with mulching and hydrogel polymer; these authors found that applying 1.5 g dm -3 of the polymer increased leaf chlorophyll indices.…”
Section: Chlorophyl Indicessupporting
confidence: 60%
See 3 more Smart Citations
“…Hydro-absorbent polymers can absorb and retain a large amount of water and fluids, reducing nutrient losses by leaching, such as nitrogen, which is a constituent element of chlorophyll molecules (Felippe et al, 2016(Felippe et al, , 2020 and is present in fertilizers such as urea and organic matter. Comparable results were obtained by Araújo et al (2022) in yellow passion fruit cv. BRS GA1 irrigated in soil with mulching and hydrogel polymer; these authors found that applying 1.5 g dm -3 of the polymer increased leaf chlorophyll indices.…”
Section: Chlorophyl Indicessupporting
confidence: 60%
“…The larger planting hole volume has high interaction with increased irrigation depth due to the greater water supply provided by the irrigation depth in a larger volume of soil explored by the roots of yellow passion fruit plants, as roots are concentrated within the topmost soil layer up to 40 cm deep (Sousa et al, 2005;Lucas et al, 2012;Rosa et al, 2017). Araújo et al (2022) also found that the application of hydro-absorbent polymer doses associated with mulching increased leaf transpiration in yellow passion fruit plants irrigated with maximum water depth.…”
Section: Gas Exchangementioning
confidence: 85%
See 2 more Smart Citations
“…Passiculture has great socioeconomic importance for the semiarid region of the Brazilian Northeast; however, water in this region is the most limiting factor for obtaining high yields, due to high evaporative rates and irregular distribution of rainfall, making it necessary to use irrigation [ 4 , 5 ]. However, the use of water by agricultural crops is considered very low, as approximately 60% of the applied water, depending on the irrigation method, is lost by evaporation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%